THE INFLUENCE OF COMPANY SIZE ON AUDIT REPORT LAG IN COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE - Kibet Lesmana, Kusnadi; Ikhram, Faisal; Bahtera Syah, Zhillan (Accounting Research Journal, 2024)
A financial report audit has the aim of providing an opinion regarding the fairness and conformity of financial reports with applicable principles. Financial report audits are carried out to provide assurance of the reliability of financial reports. Financial reports are a means of communication and accountability for internal company parties to external parties, especially for companies that go public. Company financial reports contain information that is a tool for stakeholders and users of financial reports in making decisions. To ensure that financial reports are useful in decision making, reliability and timeliness (relevance) are very important. If there is a delay in reporting financial reports, this can affect users of financial reports in making decisions and predictions.